Global fecal and plasma metabolic dynamics related to Helicobacter pylori eradication - Yap T.W.-C.; Leow A.H.-R.; Azmi A.N.; Callahan D.L.; Perez-Perez G.I.; Loke M.-F.; Goh K.-L.; Vadivelu J. (Frontiers Research Foundation, 2024)
Indexed by WOS/SCOPUS/ERA